Financial ratio and company size to mining company's CSR disclosure - Sriyatun, Sriyatun; Hariyanti, Widi; Harjito, Yunus (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
Corporate social responsibility is a company's obligation to conduct business operations, not to harm the environment. Companies carry out CSR activities to show their commitment to operating ethically, not violating the law, and contributing to society. Research on CSR in companies is still being debated and offers various findings, so it is still attractive for more depth analysis. This study aims to analyze the effect of profitability, leverage, liquidity, and company size on corporate social responsibility (CSR) disclosure. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2017–2021 period. The sample in this study amounted to 79 samples obtained from 17 companies over five years using a purposive sampling method. The results show that profitability does not affect CSR disclosure, leverage has a negative effect on CSR disclosure, liquidity does not affect CSR disclosure, and firm size has a positive impact on CSR disclosure.